Charlemagne : the formation of a European identity - McKitterick, Rosamond (Cambridge University Press, 2008)
Charlemagne is often claimed as the greatest ruler in Europe before Napoleon. This magisterial study re-examines Charlemagne the ruler and his reputation. It analyses the narrative representations of Charlemagne produced after his death, and thereafter focuses on the evidence from Charlemagne's lifetime concerning the creation of the Carolingian dynasty and the growth of the kingdom, the court and the royal household, communications and identities in the Frankish realm in the context of government, and Charlemagne's religious and cultural strategies. The book offers a critical examination of the contemporary sources and in so doing transforms our understanding of the development of the Carolingian empire, the formation of Carolingian political identity, and the astonishing changes effected throughout Charlemagne's forty-six year period of rule. This is a major contribution to Carolingian history which will be essential reading for anyone interested in the medieval past. Rosamond McKitterick has also received the 2010 Dr A.H. Heineken Prize for History for her research into the Carolingians.